Large mutual fund families: Bigger may not always be better - Singapore Management University (Institutional Knowledge at Singapore Management University, 2012)
Size is not everything but it may be intuitive for the novice investor to place his money in a mutual fund from large fund families thinking that it will outperform the smaller ones.